(untitled) (Medicine Today, 2015)
This Prospective study is designed to investigate the efficacy of conjunctival autograft in surgical management of primary pterygium. The study was conducted at Tairunnessa Memrial Medical College and Hospital, Targach, Board bazar,Tongi, Gazipur and Kushtia General Hospital from July 2012 to June 2013. Fifty eyes with primary pterygia were selected for the study.Ptergium was graded depending on the extent of corneal involvement. We excluded the patients with recurrent pterygium, double headed pterygium, dry eye and history of previous intraocular surgery from our study. The mean patient age at the time of surgery was 41.9±8.1 years ranged from 30 to 60 years.The excision of pterygium with conjunctival autograf was done under peribulbar anaesthesia using 8-0 virgin silk.Then the patients were followed up for 12 months. The excision of pterygium with conjunctival auto graft was done by applying same technique. All grafts were intact during the follow up period. There is recurrence in three patients that becomes evident within first three month. Conjunctival autograft is a effective surgical technique for the treatment of pterygium.It is safe and uncomplicated procedure and prevents the recurrence of pterygium. It also reduces the risk of granuloma formation, scleral thinning and necrosis. Medicine Today 2014 Vol.26(2): 75-77